2010
DOI: 10.1021/ie9006529
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Selectivity of Nanostructured Sulfur-Doped Pd/SBA-15 Catalyst for Vegetable Oil Hardening

Abstract: Sunflower and canola oils were hardened over a novel sulfur-promoted Pd catalyst. The formulated catalyst comprised of 0.7 wt % palladium nanoparticles promoted with 0.3 wt % sulfur highly dispersed on mesoporous silica SBA-15 (0.7% Pd-0.3% S/SBA-15). The effect of temperature (80-130 °C) and H 2 pressure (3.6-9.3 atm) on the activity, selectivity, and trans (TFA) and saturated (SFA) fatty acids formation were studied for both oils. Under similar temperature and H 2 -pressure conditions, sunflower and canola o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…It appears that the agitation rate and the reaction temperature have a synergetic effect in the enhancement of total CLA production. This may be attributed to better mass transfer features of oil triglycerides at the catalyst active sites owing to the reduced level in the oil viscosity and enhanced triglyceride diffusion in the catalyst pores at more elevated temperature and agitation rate (Kemache et al, 2010).…”
Section: Agitation Rate Effectmentioning
confidence: 99%
“…It appears that the agitation rate and the reaction temperature have a synergetic effect in the enhancement of total CLA production. This may be attributed to better mass transfer features of oil triglycerides at the catalyst active sites owing to the reduced level in the oil viscosity and enhanced triglyceride diffusion in the catalyst pores at more elevated temperature and agitation rate (Kemache et al, 2010).…”
Section: Agitation Rate Effectmentioning
confidence: 99%
“…Lower temperatures and higher pressures result in lower TFA levels [7]; however, it has not been possible to produce partially hydrogenated oils with low TFA levels. There have been numerous studies for hydrogenation of vegetable oils over supported metal catalysts, with many reports on the various modifications of nickel, palladium, and platinum catalysts to reduce TFA levels during hydrogenation [8][9][10][11][12][13][14][15][16][17][18]. For example, Li et al reported that a nickel-boron alloy catalyst has a lower TFA selectivity for the hydrogenation of soybean oil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kemache et al showed that different chemical composition of initial oil leads to the different catalyst activities under same reaction conditions (Kemache et al, 2009). It is well known that even the oils that originate from the same herbal species can have significantly different fatty acids composition (Fernández et al, 2009;Naglič et al, 1998;Rudan-Tasic and Klofutar, 1999).…”
Section: Rate Constants and Reaction Pathwaysmentioning
confidence: 99%
“…Although, amount of trans fatty acids produced during the process of oil hydrogenation, depends of the activity of used catalysts (McArdle et al, 2014) optimization parameter which increases activity also leads to the increased trans content (Kemache et al, 2009;Plourde et al, 2004;Rylander, 1970).…”
Section: Rate Constants and Reaction Pathwaysmentioning
confidence: 99%